Gaya Kepemimpinan Transaksional dan Transformasional terhadap Kinerja Karyawan Farmasi di UPTD Puskesmas Sumbersari - Siti Aminah; Andri Mardi Susanto; Harmawan Teguh Saputra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the application of transactional and transformational leadership styles and their impact on the performance of pharmacy employees at the Sumbersari Community Health Center (UPTD). The research method used was descriptive research with a qualitative approach. Data collection was conducted through observation, in-depth interviews, and documentation involving eight informants selected using purposive sampling techniques until data saturation was achieved. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. Data validity was tested through triangulation of sources, techniques, and time. The results indicate that the leadership style applied at the Sumbersari Community Health Center (UPTD) tends toward transformational leadership, characterized by participatory decision-making, open communication, continuous motivation, exemplary leadership, and attention to employee development. This leadership style has a positive impact on improving pharmacy employee performance, as reflected in punctuality, independence, effectiveness, quality, and quantity of work. The conclusion of this study indicates that transformational leadership supported by the situational application of transactional leadership can improve the performance of pharmacy staff and support the effectiveness of pharmaceutical services at the Sumbersari Community Health Center (Puskesmas UPTD). Keywords: Transformational Leadership, Transactional Leadership, Employee Performance, Pharmaceutical Services, Community Health Center